Urban agriculture as a strategy for urban resilience in developing countries - Urías Borbón, Diana Susana (Centro Universitario de Arte, Arquitectura y Diseño, 2020)
Throughout history and numerous recent experiences, urban gardens have been used to mitigate the impact of economic, environmental and even social crises in cities, especially those located in developing countries. This paper analyses various examples of urban orchard-gardens implemented as a strategy to increase resilience in cities from Africa, Asia and Latin America, each with different economic, social and climatic contexts, with the aim of identifying practices that can be replicated in similar contexts. From economic resilience (surviving moments of crisis and/or war), social resilience (integration of vulnerable sectors of the population) and environmental resilience (coping with natural phenomena), urban orchard-gardens have proved to be a viable strategy for resolving these issues. As they are implemented in areas that cannot be built on due to flood risk, such as riverbanks, they function as a natural barrier and water absorption area. In some cities, the crops can represent important family savings and improve food quality. Furthermore, their use as a strategy for generating employment and reducing insecurity, exemplifies that urban orchard-gardens are an effective and economic strategy, contributing to the economic, social and environmental resilience of today’s cities.